THE INFLUENCE OF EMPLOYEE TURNOVER INTENSITY, FINANCIAL ACCOUNTING SYSTEM IMPLEMENTATION, AND DIRECT SUPERVISION ON CORPORATE PERFORMANCE ACCOUNTABILITY, WITH EFFECTIVE WORK CULTURE AS A MODERATING VARIABLE, AT COMPANY XX IN 2026. (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
Competitive dynamics in the corporate sector demand radical changes in corporate governance systems to maintain stakeholder trust. Performance accountability is no longer viewed merely as an instrument for bureaucratic compliance or formal paper-based reporting; rather, it is a comprehensive manifestation of an organization's commitment to managing every aspect of its resources efficiently, transparently, and responsibly. This study employs a quantitative approach with an associative-causal design. Data were collected via a survey method involving the distribution of structured, Likert-scale questionnaires to employees of Company XX. Statistical data analysis and hypothesis testing were conducted using component-based Structural Equation Modeling (SEM) via SmartPLS version 4.0. The study population comprised all 90 permanent and contract employees within the operations, finance, and administration divisions of Company XX in 2026; a saturated sampling (census) technique was applied. The research findings indicate that: Employee Turnover Intensity has a significant negative effect on Corporate Performance Accountability; the Implementation of the Financial Accounting System has a significant positive effect on Corporate Performance Accountability; and Inherent Supervision does not have a significant effect on Corporate Performance Accountability. Furthermore, Effective Work Culture does not significantly mediate the effect of Employee Turnover Intensity, the Implementation of the Financial Accounting System, or Inherent Supervision on Corporate Performance Accountability.